Implementasi model case method dalam meningkatkan inovasi pembelajaran mahasiswa dan kemampuan berpikir kritis pada mata kuliah teknik perdagangan Internasional - Hodijah, Siti; Hastuti, Dwi; Zevaya, Faradina (Jurnal Paradigma Ekonomika, 2022)
This study analyzes how the case method improves learning innovation among students by improving critical thinking skills in International trade technique. This is motivated by the large number of students with various problems related to the ability to be critical and active in each lecture. Therefore, towards students' critical thinking skills in international trade engineering courses through the application of a discussion-based participatory learning model to solve cases or problems or case-based methods. The design used in this study is a One-Shot Case Study experimental design. Where in the implementation of the International trade technique course, students of the Development Economics Study Program use learning using the case method. After observing the results in the form of students' critical thinking skills in class, it can be seen that there is a student's desire to help sharpen, think critically, conduct discussions, communicate with friends and lecturers in solving problems that are appointed as case studies. The results of this study indicate that through the application of the case method learning model or case study it is able to encourage students' creative and critical thinking skills in solving cases from various different points of view so as to bring up the best solution.